Development of new Mg-Zn-Sr alloys for medical purpose. (10th November 2020) - Šuliková, Michaela; Molčanová, Zuzana; Ballóková, Beata; Ďurišin, Juraj; Martinková, Slávka; Varcholová, Dagmara; Michalik, Štefan; Tang-Kong, Robert; Ward, Logan; Mehta, Apurva; Šuľová, Katarína; Fejerčák, Miloš; et al.
In surgery, in addition to joint replacement, which requires permanent implantation of the prosthesis into the human body, there are many other clinical cases where fixation or mechanical support are only temporarily needed during the healing process of the injured or pathological tissue. In this case, biodegradable materials are the optimal choice as these materials do their job and degrade in the human body thereafter. Amorphous magnesium-zinc based alloys are nowadays a very promising group of metallic glasses (MGs). Unfortunately, the brittleness of Mg-Zn MGs and poor glass forming ability (GFA) have hindered their further application. We have developed a composition series of completely new (not published) ternary Mg-Zn-Sr alloys with attractive properties in terms of possible future applications (density comparable to human bones, wide supercooled liquid region, low rate of degradability, etc.). These ternary alloys will serve as precursors for design of future highly alloyed systems with tuned mechanical properties and dissociation rate in human body.